Short Chain Fatty Acid (SCFA) Gut Biota and Interleukin 6 (IL-6) Related to the Severity of Systemic Lupus Erithematosus (SLE) at Dr. Mohammad Hoesin General Hospital Palembang - Edwin Nugraha Fitriawan; Eddy Mart Salim; Erial Bahar; Nova Kurniati; Yuniza; Syamsu Indra; Norman Djamaludin (HM Publisher, 2022)
Background. SLE is an autoimmune disease characterized by the presence of autoantibodies in the nucleus, deposition of immune complexes, and can attack various body tissues. Gut biota in this case short-chain fatty acids (SCFA) play a role in the inflammatory process in the SLE, while the levels of IL- 6 can also be associated with a response to inflammation which will be seen in the degree of SLE activity. This study aims to determine the correlation of SCFA Gut biota and IL - 6 with SLE degree activity. Methods. This study is a cross-sectional study with a correlation test design, conducted from November 2021-January 2022 at RSMH Palembang with the research subjects being all SLE patients seeking treatment at the Allergy-Immunology Division of RSMH Palembang with categories of mild and moderate-severe SLE activity degree. Examination of SCFA Gut biota using stool samples and serum IL-6 levels were associated with SLE activity degree. Statistical analysis of the correlation test with Spearman for numerical data not normally distributed, and continued with linear regression test to assess the multivariate analysis in this study. Results. The sample consisted of 32 patients, every 16 patients with mild and moderate-severe SLE activity degrees. The correlation between SCFA Gut biota with SLE activity degree was found to have a correlation coefficient of r=-0.777 with p=0.000. Correlation between IL-6 with SLE activity degree obtained a correlation coefficient of r=0.910 with p=0.000, while the correlation test between IL-6 and SCFA Gut biota obtained r=-0.633 with a value of p=0.000. Multivariate analysis found that 70.5% of SCFA Gut biota and IL-6 affected SLE activity degree. Conclusion. SCFA Gut biota and IL-6 had a significant correlation in statistical tests with the SLE activity degree.